Effectiveness Test of Ketapang Leaf Extract (Terminalia Catappa L.) as a Hepatoprotective Agent in Mice (Mus musculus) Induced by Acetaminophen - Anjani, Desak Sri Ayu; Indriani, Nurul; Kresnapati, I Nyoman Bagus Aji (Jurnal Multidisiplin Sahombu, 2025)
Drug-induced liver injury (DILI) is a leading cause of acute liver failure, with acetaminophen being the most frequent etiological agent. Overdose induces formation of the toxic metabolite N-acetyl-p-benzoquinone imine (NAPQI), resulting in glutathione depletion, oxidative stress, and hepatocellular necrosis. This study aimed to evaluate the hepatoprotective effect of ethanolic extract of Terminalia catappa L. leaves in male mice (Mus musculus) with acetaminophen-induced acute liver injury. A post-test only control group design was employed using 20 mice divided into five groups: negative control (Na-CMC), positive control (N-acetylcysteine), and three treatment groups receiving T. catappa extract at doses of 200, 400, and 600 mg/kg BW. Acetaminophen was administered intraperitoneally at 500 mg/kg BW. Serum SGPT and SGOT levels were quantified spectrophotometrically, and phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, tannins, and terpenoids. Extract administration significantly (p < 0.05) reduced SGPT and SGOT levels compared to the negative control, with a clear dose-dependent trend; the 600 mg/kg BW group achieved biochemical parameters approaching those of the N-acetylcysteine group. The hepatoprotective effect is likely mediated by flavonoid-driven antioxidant and anti-inflammatory mechanisms. These findings indicate that T. catappa extract is a promising, safe, and cost-effective plant-based hepatoprotective agent, meriting further investigation toward clinical application as an adjunct therapy for drug-induced hepatotoxicity